Optimization a Scheduling Algorithm of CA in LTE ADV - Sarmad K. Ibrahim; Nasser N. Khamiss (Universitas Ahmad Dahlan, 2018)
Long-Term Advancement Progressed (LTE-ADV) is the advancement of the long-term evolution, which created via 3GPP. LTE-ADV aims to offer a transmission bandwidth of (100) MHz by using Carrier Aggregation (CA) to aggregate LTE-ADV carriers. To increase the data capacity of the system and resource allocation converts a very good tool. LTE-Advanced multiple Component Carriers (CCs) becomes a difficult optimization problem. In the paper proposes a new scheduling algorithm and compares with a different scheduling traditional algorithms that are proportional fair and round robin in the CA, in order to find the best scheduler that provides high-quality throughput and improves fairness. It i also evaluates mapping model types are Mutual Information Effective SINR Mapping (MIESM) and Exponential Effective SINR Mapping (EESM). The results show that the throughput in the proposed algorithm with MIESM outperforms from others mapping and scheduling.